Sulphur in the metal poor globular cluster NGC 6397 - Koch-Hansen, Andreas; Caffau, Elisabetta (Astronomy and astrophysics, 2011)
Sulphur (S) is a non-refractory α-element that is not locked into dust grains in the interstellar medium. Thus no correction to the measured, interstellar sulphur abundance is needed and it can be readily compared to the S content in stellar photospheres. Here we present the first measurement of sulphur in the metal poor globular cluster (GC) NGC 6397, as detected in a MIKE/Magellan high signal-to-noise, high-resolution spectrum of one red giant star. While abundance ratios of sulphur are available for a larger number of Galactic stars down to an [Fe/H] of ~ −3.5 dex, no measurements in globular clusters more metal poor than −1.5 dex have been reported so far. We find aNLTE, 3-D abundance ratio of [S/Fe] = +0.52 ± 0.20 (stat.) ± 0.08 (sys.), based on theS I, Multiplet 1 line at 9212.8 Å. This value is consistent with a Galactic halo plateau as typical of other α-elements in GCs and field stars, but we cannot rule out its membership with a second branch of increasing [S/Fe] with decreasing [Fe/H], claimed in the literature, which leads to a large scatter at metallicities around − 2 dex. The [S/Mg] and [S/Ca] ratios in this star are compatible with a Solar value to within the (large) uncertainties. Despite the very large scatter in these ratios across Galactic stars between literature samples, this indicates that sulphur traces the chemical imprints of the other α-elements in metal poor GCs. Combined with its moderate sodium abundance ([S/Na]NLTE = 0.48), the [S/Fe] ratio in this GC extends a global, positive S-Na correlation that is not seen in field stars and might indicate that proton-capture reactions contributed to the production of sulphur in the (metal poor) early GC environments.